Given: A = (½) * (b1 + b2) * h ;
________________________________
→Multiply EACH side of the equation by "2", to get rid of the fraction, "½";
____________________________________________________________
→ 2*A = 2 * (½) * (b1 + b2) * h ;
→ 2* A = 1 * (b1 + b2) * h ;
→ 2A = (b1 + b2) * h ;
____________________________
→ Now, divide EACH side of the equation by: "(b1 + b2)" ; to isolate "h" on one side of the equation;
__________________________________________________________
→ 2A / (b1 + b2) = [(b1 + b2) * h] / (b1 + b2) ;
→ 2A / (b1 + b2) = h ; ↔